تسيير الهياكل والمنشآت الرياضية من الجماعات المحلية وآليات تحقيق أهداف الرياضة للجميع - دراسة ميدانية لولاية بجاية - عمران لامين; Supervisor بوصلاح نذير (Mohamed Boudiaf University of M'sila, 2024)
الملخص : بالعربية (عبارة عن فقرة ): إن إحدى سمات الحياة الحديثة الموجودة في كافة ثقافات العالم الأهمية المتزايدة للمنظمات والمنشآت والمؤسسات وإذا ما أردنا للرياضة تزدهر وتتقدم فلابد من أن تتخذ العلم طريقا و الإدارة هي أحد الأعمدة العلمية الأساسية التي تعتمد عليها كافة الدول المتقدمة ومنشآتها ومؤسساتها في النهوض بالرياضة وإن عالم الرياضة لا يختلف عن ذلك في هذا الصدد والمردود الرياضي يتغير باستمرار نتيجة لتغيير المنظمات والمنشآت. والشيء الجدير بالاهتمام هو الدور الذي تلعبه الجماعات المحلية في تطوير الرياضة للجميع وترقيتها من خلال التسيير الجيد من جهة، والدعم المادي والمعنوي من جهة أخرى لتحقيق نتائج النهوض بالرياضة الترويحية وإن الجماعات المحلية حلقة الربط الأساسية بين الدولة والأفراد. وفي هذا العدد نحاول من خلال دراستنا هذه، التعرف حول" تسيير الهياكل والمنشآت الرياضية من الجماعات المحلية وآليات تحقيق أهداف الرياضة للجميع." - عنوان الدراسة :تسيير الهياكل والمنشآت الرياضية من الجماعات المحلية وآليات تحقيق أهداف الرياضة للجميع دراسة ميدانية لولاية بجاية. أهداف الدراسة : - الوصول إلى معرفة آليات تسيير الهياكل والمنشآت الرياضية من الجماعات المحلية يساهم في تحقيق أهداف الرياضة للجميع. - الوصول إلى معرفة ما إذا كان يساهم المورد البشري المتخصص المسير للهياكل المنشآت الرياضية يساهم في تحقيق أهداف الرياضة للجميع. - الوصول إلى معرفة ما إذا كانت الجماعات المحلية توفر كافة الإمكانات المالية والمادية والتي تساهم في تحقيق أهداف الرياضة للجميع. التساؤل العام للدراسة : هل آليات تسيير الهياكل والمنشآت الرياضية من الجماعات المحلية يساهم في تحقيق أهداف الرياضة للجميع ؟ التساؤلات الجزئية : - هل كفاءة المسير للهياكل والمنشآت الرياضية تساهم في تحقيق أهداف الرياضة للجميع؟ - هل تعتمد الجماعات المحلية في تسيير الهياكل والمنشآت الرياضية على برمجة دورية تساعد في تحقيق أهداف الرياضة للجميع؟ - هل توفر الجماعات المحلية كل الإمكانات اللوجيستيكية بالمنشآت الرياضية لتحقيق أهداف الرياضة للجميع؟ الفرضية العامة للدراسة : الفرضيات الجزئية - يتميز مسيرو الهياكل والمنشآت الرياضية لكفاءة عالية تساهم في تحقيق أهداف الرياضة للجميع. - تسطر الجماعات المحلية برمجة دورية آلية في تسيير الهياكل والمنشآت الرياضية لتحقيق الأهداف. - تسعى الجماعات المحلية إلى توفير كل الإمكانات المادية والبشرية لتحقيق أهداف الرياضة للجميع. المنهج المتبع في الدراسة : تمت الدراسة باستخدام المنهج الوصفي. الأدوات المستخدمة في الدراسة : تم استخدام أداة الاستبيان كوسيلة لجمع البيانات والمعلومات. الكلمات المفتاحية بالعربية : المنشآت الرياضية، الجماعات المحلية، الرياضة للجميع، التسيير. بالإنجليزية ........................................................................................ جاء هذاالبحث في فصول . الفصل الأول :المنشآت الرياضية وتناول الفصل الثاني :الجماعات المحلية أماالفصل الثالث: الرياضة للجميع الفصل الرابع: الفصل التطبيقي من أهم النتائج التي توصل إليها الباحث : - تحقيق الاهداف يعتمد بالدرجة الأولى على كفاءات وفعالية عالية. - تسيير الأمثل في اتخاذ القرارات لتحقيق أهداف المنشأة. - اختيار الموقع الملائم والأنسب لإنشاء منشأة رياضية . - إبراز دور الجماعات المحلية في تسيير هياكل المنشآت الرياضية. - تلعب الجماعات المحلية دور هام في تحقيق آليات وأهداف الرياضة للجميع. - وجوب الاهتمام بالموارد البشرية كعامل لتحقيق أهدافها. - توفير كل الإمكانيات المادية والبشرية يؤدي إلى تحقيق أهداف الرياضة للجميع. أهم التوصيات:  تشجيع الأفكار الجديدة المفيدة لتحسين تسيير النابعة في الأفراد العاملين في المنشأة الرياضية وعلى كافة المستويات لتحقيق أهداف الراضة للجميع.  تسطير برامج يضمن وضع آليات واضحة المعالم تستند إلى منهجية علمية بحثة تأحذ بعين الاعتبار جميع العوائق والمسببات التي تعيق التسيير الحسن للمنشآت.  زيادة الاهتمام بالعنصر البشري داخل المنشآت.  على المسير انتهاج السبل والوظائف الملائمة لتسيير الأمثل للمنشآت الرياضية لتحقيق لأهداف الرياضة للجميع.  وضع إدارة رياضية تهتم بتكوين الإطارات في مجال التسيير.  تأسيس جمعيات رياضية موجهة لتنشيط الممارسة الرياضية.  إشراك مختصون في مجال الرياضة لتنشيط الممارسة الرياضية على مستوى الرابطات الولائية للرياضة للجميع.  النهوض بالرياضة بصفة عامة والحركة الرياضية الجمعوية بصفة عامة.  تدعيم الجمعيات والنوادي الرياضية وذلك لخلق التنافس وزرع حب التفوق لتحقيق أهداف الرياضة للجميع. Searchlight in English Faculty Institute of Sciences and Sports and Technical and Physical Activities Department: Order No:......................................................... No. d 'registration : ............................................... .................................. Searcher : ............................ ......AMRANE Lamine................................. Publicly supported on :............................................................................ Title of the thesis (dissertation): Managing sports structures and facilities of groups Local issues and mechanisms for achieving the goals of sports for all. -A field study of Bejaia Province- Language of the thesis: ............................. Arabic............................................... Model of the thesis: ....................................:Master.............................................. Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor: Mr BOUSLAH Nadir. Grade: Doctor. Lecturer Number of pages: .....................................103................... Option: Management of sports facilities and human resources. Summary: One of the features of modern life that is present in all cultures of the world is the increasing importance of organizations, facilities and institutions. If we want sport to flourish and advance, it must take science as a path, and management is one of the basic scientific pillars on which all developed countries and their facilities and institutions depend in promoting sport, and the world of sports is no different. In this regard, the sporting performance is constantly changing as a result of changing organizations and facilities. What is noteworthy is the role played by local groups in developing and promoting sports for all through good management on the one hand, and material and moral support on the other hand to achieve the results of promoting recreational sports. Local groups are the basic link between the state and individuals. In this issue, we attempt, through our study, to learn about “the management of sports structures and facilities by local communities and the mechanisms for achieving the goals of sports for all.” Title of the study: Management of sports structures and facilities by local groups and mechanisms for achieving the goals of sports for all: A field study for the state of Bejaia. The purpose of the study: - Access to knowledge of the mechanisms for managing sports structures and facilities from local groups contributes to achieving the goals of sports for all. - Getting to know whether the specialized human resource managing the structures and sports facilities contributes to achieving the goals of sports for all. - Finding out whether local groups provide all the financial and material capabilities that contribute to achieving the goals of sports for all. Problem: - Does the efficient management of sports structures and facilities contribute to achieving the goals of sports for all? In managing sports structures and facilities, do local groups rely on periodic programming that helps achieve the goals of sports for all? - Do local groups provide all the logistical capabilities in sports facilities to achieve the goals of sports for all? Hypotheses: 1- Managers of sports structures and facilities are distinguished by their high efficiency, which contributes to achieving the goals of sports for all. 2 - Local groups establish automatic periodic programming in the management of sports structures and facilities to achieve goals. 3- Local groups seek to provide all the material and human capabilities to achieve the goals of sports for all. Key words : Sports facilities, local groups, sports for all, management. - The most important results achieved are: -Achieving goals depends primarily on high competencies and effectiveness. - Optimal management of decision-making to achieve the organization’s objectives. - Choosing the appropriate and most appropriate location to establish a sports facility. - Highlighting the role of local groups in managing the structures of sports facilities. Local groups play an important role in achieving the mechanisms and goals of sports for all. - It is necessary to pay attention to human resources as a factor in achieving its goals. - Providing all material and human capabilities leads to achieving the goals of sports for all.
Keywords: المنشآت الرياضية; الجماعات المحلية; الرياضة للجميع; التسيير